Некоторые особенности контактного взаимодействия инструмента с заготовкой при деформирующем протягивании с вращением инструмента - Розенберг, О.А.; Шейкин, С.Е.; Ростоцкий, И.Ю. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
The article is devoted to research of features of contact interaction of the tool with detail, at deforming broaching with rotation of the tool. Results of researches of interaction of the tool are brought with processable by a product: axial forces, a roughness, extent of contact, microhаrdness.